Innovation and traditionalism in Hooshang Ebtehaj,s lyric poems - نجمه نوروزی; سعید حاتمی; جلیل شاکری (مطالعات زبانی و بلاغی)
AmirHooshang Ebtehaj (Saye) is a powerful and proficient poet. He is one of the best and most well known contemporary composers of lyric poems. He has tested both poetic styles: traditional and nimaeian. So, it is really normal that composer his lyric poems is influenced by his nimaean poems and it became one of the best composers of new lyric poems. Although, lyric poem, new or traditional is a kind of poet and we can consider it in five areas: sentiment, language, imagination, music and form. Researchers in this study try to consider Ebtehaj,s poem in these five areas separately in order to find that how much innovation he has had in each area ?and how much he has followed special poem qualities of traditional poets like Hafez, Saadi, and Molana. According to this study, Saye's lyric poems has elegant and poetical sentiment , furthermore his poets form and music perform traditional poets. Also, about sentiment and mental images has admirable innovations and in language and imagination area has a little innovations.